Radiation Effects on Decreased Estrogen with Isoflavone Consumption to Prevent Early Menopause in Radiation Therapy - Yeni Cahyati; Didik Rahadi Santoso; Unggul P Juswono (Natural B, Journal of Health and Environmental Sciences, 2013)
Radiation effect is one of which is the reduction in estrogen. Gamma rays are ionizing radiation that can lead to cell damage due to free radicals produced when the radiation interacts with cells. The level of cell damage can be minimized by antioxidants. Antioxidants used is the isoflavones of soy milk, so it can be know the effects of radiation on the decline in estrogen that accompanied the consumption of isoflavones to prevent early menopause in radiation therapy.Radiation exposure are given fractionally. The dose was 1,5 Gy in once exposure and given every 3 days up to a maximum dose of the treatment groups. Consumption of soy milk to the mice done orally. Blood was drawn and serum was made. Serum estrogen levels will be tested by using ELISA.The results showed that the ovarium disfunction and stress experienced by mice (Mus musculus) caused by radiation exposure. Maximum results in the consumption of isoflavones on estrogen levels the subject to radiation exposure is 44 mg/day and 131 mg/day of soy milk. This isoflavone dose increase in estrogen levels maximumly. The increase was the response given by the body's immune system of mice due to start reacting and isoflavones are phytoestrogens.